A randomised, controlled, double blind study to assess mechanistic effects of combination therapy of dapagliflozin with exenatide QW versus dapagliflozin alone in obese patients with type 2 diabetes mellitus (RESILIENT): study protocol. Issue 7 (20th July 2021) - Brown, Emily; Wilton, Moon M; Sprung, Victoria S; Harrold, Joanne A; Halford, Jason C G; Stancak, Andrej; Burgess, Malcolm; Howarth, Elaine; Umpleby, A Margot; Kemp, Graham J; Wilding, John PH; Cuthbertson, Daniel J
Abstract : Introduction: The newer glucose-lowering therapies for type 2 diabetes (T2D), the glucagon-like peptide-1 receptor agonists (GLP1-RAs) and the sodium-glucose co-transporter 2 inhibitors (SGLT2i), have additional clinical benefits beyond improving glycaemic control; promoting weight loss, addressing associated cardiovascular risk factors and reducing macrovascular and microvascular complications. Considering their independent mechanisms of actions, there is a potential for significant synergy with combination therapy, yet limited data exist. This 32-week randomised, double-blind, placebo-controlled trial will gain mechanistic insight into the effects of coadministration of exenatide QW, a weekly subcutaneous GLP1-RA, with dapagliflozin, a once daily oral SGLT2i, on the dynamic, adaptive changes in energy balance, total, regional and organ-specific fat mass and multiorgan insulin sensitivity. Methods and analysis: 110 obese patients with diagnosed T2D (glycated haemoglobin, HbA1c ≥48 mmol/mol) will be treated for 32 weeks with dapagliflozin (10 mg once daily either alone or in combination with exenatide QW (2 mg once weekly); active treatments will be compared with a control group (placebo tablet and sham injection). The primary objective of the study is to compare the adjusted mean reduction in total body fat mass (determined by dual-energy X-ray absorptiometry, DEXA) from baseline following 32 weeks of treatment with exenatide QW and dapagliflozin versus dapagliflozin alone compared with control (placebo). Secondary outcome measures include changes in (1) energy balance (energy intake and energy expenditure measured by indirect calorimetry); (2) appetite (between and within meals) and satiety quotient; (3) body composition including visceral adipose tissue, subcutaneous adipose tissue, liver and pancreatic fat. Exploratory outcome measures include metabolic changes in hepatic and peripheral insulin sensitivity (using a two-stage hyperinsulinaemic, euglycaemic clamp), central nervous system responses to food images using blood oxygen level-dependent (BOLD) functional MRI (fMRI) and changes in cardiovascular function (using transthoracic echocardiography, cardiac MR and duplex ultrasonography). Ethics and dissemination: This study has been approved by the North West Liverpool Central Research Ethics Committee (14/NW/1147) and is conducted in accordance with the Declaration of Helsinki and the Good Clinical Practice. Results from the study will be published in peer-reviewed scientific and open access journals and/or presented at scientific conferences and summarised for distribution to the participants. Trial sponsor: University of Liverpool. Trial registration number: ISRCTN 52028580; EUDRACT number 2015-005242-60.